Enthusiastic Study of Children of Indonesia Migrant Workers in Selangor, Malaysia Who Do Not Have Access to Formal Education - Rianti rianti; Ardhana Zanuar Mahardani; Hadi Cahyono; Wiffy Zalina Putri (Journal of Social Research, 2024)
The purpose of this study is to provide a description of the results of observations on the children of Malaysian migrant workers, especially about the enthusiasm or enthusiasm for learning children not only learning about understanding social sciences but one of them is learning religious science through religious science lessons and forms of application in the form of daily prayers, prayer readings, recitations and da'wah practices in the form of lectures. This material not only conveys the knowledge but also in practice and application as well as the way of delivery and good and correct lecture techniques, besides that also with lectures children can learn public speaking, speaking in public with good and directed conduct. Indonesia's children are future leaders and future generations of the Indonesia nation for the next 10 years, therefore the position of the young generation of Indonesia's children is very much needed. The enthusiasm for learning children in the Sungai Buloh area of Selangor has a very extraordinary spirit of learning. Most of the residents of the community in the Sungai Buloh Selangor area are Indonesia citizens who have lived in Malaysia, so there are quite a lot of children aged 7-13 years who are in elementary school. The Sungai Buloh Learning Studio is one of the main avenues for children of migrant workers to learn social and religious sciences, most of the people in the Sungai Buloh area of Selangor lack access to education due to their incomplete documents so that it is difficult for children to continue to public schools in Kuala Lumpur, this is one of the things that is worrisome because of the lack of access to education for the children of Indonesia migrant workers who are domiciled in the Sungai Buloh region of Selangor, Malaysia. With the enthusiasm of good children to learn but hindered by their incomplete documents, access to education for migrant workers living in the Sungai Buloh Selanggor area, Malaysia is quite difficult.